Common Symptoms from an Uncommon Infection: Gastrointestinal Anisakiasis - Yuto Shimamura; Niroshan Muwanwella; Sujievvan Chandran; Gabor Kandel; Norman Marcon (Canadian Journal of Gastroenterology and Hepatology)
Clinicians can be forgiven for thinking of anisakiasis as a rare condition low in the differential diagnosis of abdominal pain. Gastrointestinal anisakiasis is a zoonotic parasitic disease caused by consumption of raw or undercooked seafood infected with nematodes of the genus Anisakis. Even though the reported cases indicate that this is a rare disease, the true incidence of the disease could be potentially higher than what is reported in the literature as cases can go undiagnosed. Diagnosis and treatment of gastric anisakiasis are made by a compatible dietary history, direct visualization, and removal of the larvae via gastroscopy. Serologic testing and imaging studies are useful in the diagnosis of intestinal anisakiasis and conservative management should be considered. This disease may mimic other diseases and lead to unnecessary surgery. This emphasizes the importance of suspecting gastrointestinal anisakiasis by history taking and by other diagnostic modalities.